Development of Visible-Light Driven Cu(I) Complex Photosensitizers for Photocatalytic CO2 Reduction - Takeda, Hiroyuki; Monma, Yu; Sugiyama, Haruki; Uekusa, Hidehiro; Ishitani, Osamu (Frontiers in Chemistry, 2019)
The visible-light responsive Cu(I)-complex photosensitizers were developed by introducing various aromatic substituents at the 4,7-positions of a 2,9-dimethyl-1,10-phenanthroline (dmp) ligand in a heteroleptic CuI(dmp)(DPEphos)+-type complexes (DPEphos = [2-(diphenylphosphino)phenyl]ether) for photocatalytic CO2 reduction. Introducing biphenyl groups (Bp-) on the dmp ligand enhanced the molar extinction coefficient (ε) of the metal-to-ligand charge transfer (MLCT) band in the visible region (ε = 7,500 M–1cm–1) compared to that of the phenyl (Ph-)-containing analog (ε = 5,700 M–1cm–1 at λmax = 388 nm). However, introducing 4-R-Ph- groups (R = the electron-withdrawing groups NC-, or NO2-) led to a red shift in the band to λmax = 390, 400, and 401 nm, respectively. Single-crystal X-ray analysis showed the Ph- groups were twisted because of the steric repulsion between the 2,6-protons of the Ph- groups and 5,6-protons of the dmp ligand. The result strongly indicated that the π-conjugation effect of the 4-R-Ph- groups is so weak that the lowering of the energy of the dmp π* orbitals is small. However, when 4-R-ph- was substituted by a 5-membered heterorings, there was a larger red shift, leading to an increase in the ε value of the MLCT absorption band. Thus, the substitution to 2-benzofuranyl- groups resulted in visible-light absorption up to 500 nm and a shoulder peak at around 420 nm (ε = 12,300 M–1cm–1) due to the expansion of π-conjugation over the substituted dmp ligand. The photocatalytic reaction for CO2 reduction was tested using the obtained CuI complexes as photosensitizers in the presence of a Fe(dmp)2(NCS)2 catalyst and 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole as a sacrificial reductant, which showed improved CO generation.